2023
DOI: 10.3389/fendo.2023.1146017
|View full text |Cite
|
Sign up to set email alerts
|

The crossroad between autoimmune disorder, tissue remodeling and cancer of the thyroid: The long pentraxin 3 (PTX3)

Abstract: Thyroid is at the crossroads of immune dysregulation, tissue remodeling and oncogenesis. Autoimmune disorders, nodular disease and cancer of the thyroid affect a large amount of general population, mainly women. We wondered if there could be a common factor behind three processes (immune dysregulation, tissue remodeling and oncogenesis) that frequently affect, sometimes coexisting, the thyroid gland. The long pentraxin 3 (PTX3) is an essential component of the humoral arm of the innate immune system acting as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Furthermore, it has been shown that PTX3 may play a role as an extrinsic tumor-suppressor gene by controlling complement-dependent and macrophage-associated tumor-promoting inflammation [47]. Its expression has been found, among others, in lung cancer, glioma, ovarian cancer, myxoid liposarcoma, prostate carcinoma, esophageal squamous cell carcinoma, and pancreatic cancer [48]. Interestingly, PTX3 has been also shown as a biomarker (prognostic indicator of short-term mortality) of clinical PASC (post-acute sequelae of SARS-CoV-2), also known as post-COVID syndrome [49,50].…”
Section: Pentraxin Familymentioning
confidence: 99%
“…Furthermore, it has been shown that PTX3 may play a role as an extrinsic tumor-suppressor gene by controlling complement-dependent and macrophage-associated tumor-promoting inflammation [47]. Its expression has been found, among others, in lung cancer, glioma, ovarian cancer, myxoid liposarcoma, prostate carcinoma, esophageal squamous cell carcinoma, and pancreatic cancer [48]. Interestingly, PTX3 has been also shown as a biomarker (prognostic indicator of short-term mortality) of clinical PASC (post-acute sequelae of SARS-CoV-2), also known as post-COVID syndrome [49,50].…”
Section: Pentraxin Familymentioning
confidence: 99%